Brain Network Connectivity Mediates Education-related Cognitive Performance in Healthy Elderly Adults - Chen, Yaojing; Qi, Di; Qin, Ting; Chen, Kewei; Ai, Meishan; Li, Xin; Li, He; Zhang, Junying; Mao, Haohao; Yang, Yiru; Zhang, Zhanjun (Current Alzheimer Research, 2019)
Background: Among the protective factors for cognitive decline related to aging and Alzheimer's disease, education level is one of the most prominent. However, the mechanisms underlying the protective effects of education on cognition remain to be elucidated. In this study, we aimed to systematically assess the role of Functional Connectivity (FC) of resting-state brain networks playing in the cognition-protection effect of education. Methods: Data from a battery of neuropsychological tests and functional magnetic resonance imaging in resting-state were acquired in 77 cognitively normal elderly participants from local communities in Beijing, China. Six resting-state networks related to primary function or complex cognition were extracted through independent component analysis. We then explored the relationships between education level, cognition, and FC of these networks. Results: We found that education level was positively associated with a wide range of complex cognitive domains including general mental status, episodic memory, language, attention, executive function and visuospatial processing, and it showed significantly negative correlations with FC of multiple areas in the Default Mode Network (DMN) and Left Frontal-parietal Network (LFP) which are related to complex cognition. And regional connectivity of DMN was significantly negatively correlated with episodic memory performance. Further mediation analysis suggested that higher education level was associated with higher episodic memory performance through lower regional connectivity of DMN. Conclusion: Our findings indicate that inhibitory modulation in the resting-state brain networks related to complex cognition is one of the main routes through which education exerts its protective effects on cognition in normal aging.
Keywords: complex cognition